The emerging role of non-coding RNAs from extracellular vesicles in Alzheimer’s disease - Yu-Zhong Xu; Ming-Gang Cheng; Xiong Wang; Yu Hu (Journal of Integrative Neuroscience, 2021)
Alzheimer’s disease is an age-dependent neurodegenerative disease. Recently, different non-coding RNAs (ncRNAs), including microRNAs, long non-coding RNAs, and circular RNAs, have been found to contribute to Alzheimer’s disease’s pathogenesis. Extracellular vehicles could be enriched in ncRNAs and in their role in mediating intercellular communication. Signatures of extracellular vesicular ncRNAs have shown them to be a potential biomarker in Alzheimer’s disease. This perspective discusses the potential role of extracellular vehicle ncRNAs in Alzheimer’s disease, providing a theoretical basis for extracellular vesicular ncRNAs in Alzheimer’s disease, from pathogenesis to diagnosis and treatment.